Validity of bedside index of severity in acute pancreatitis score in comparison with C reactive protein in assessing the severity of acute pancreatitis - Trivikraman, Ramalingam; Chayampurath, Ramesan; Malieckal, Joji I. (International Journal of Research in Medical Sciences, 2016)
Background: Acute pancreatitis is a process of acute inflammation of the pancreas usually caused by biliary stones, alcohol ingestion, metabolic factors or drugs. The assessment of the severity of acute pancreatitis has a significant role in its management. There is a need for a simple and clinically oriented severity scoring system that can predict severity of acute pancreatitis at the time of presentation. Methods: A cross-sectional study was conducted at a tertiary care centre on 100 patients diagnosed as acute pancreatitis who fulfilled the inclusion criteria. Severity index, their BISAP Score, BMI and CRP values were calculated and statistical analysis was done using SPSS 17 Software. Results: In our study, there were 100 patients with pancreatitis. 65% were alcoholic pancreatitis followed by gall stone pancreatitis (17%), idiopathic pancreatitis (13%), drug induced (1%), trauma (1%), post ERCP (1%) and malignancy (2%). On the basis of CT Severity index, it was found that 15% of alcoholic group, 8% of biliary group and 1% each of idiopathic, drug induced, trauma and malignancy group were found to have severe pancreatitis. On the basis of BISAP Score it was found that 17% in alcoholic group, 7% in gall stone group, 4% in idiopathic group, 2% in malignancy group and 1% each in drug induced and trauma group were having acute pancreatitis. With the C reactive Protein level, it was found that 16% in alcoholic group, 9% in biliary group and 1% each in idiopathic, trauma and malignancy group were found to have severe pancreatitis. The sensitivity and specificity for BISAP score were 77.8% and 84.9% and the sensitivity and specificity for CRP were 66.7% and 86.3%. The K-score was found to be 0.593 for BISAP Score and 0.524 for C - reactive protein levels. This indicates that both are in moderate agreement with the gold standard test (CT Severity Index). Conclusions: BISAP score and CRP levels are not superior to the each other in predicting severity. BISAP score can be used as a predictor of severity at admission and CRP levels ≥150 can predict severity when serially monitored during the course of admission.